2002
DOI: 10.3354/meps234119
|View full text |Cite
|
Sign up to set email alerts
|

Bleaching effect on regeneration and resource translocation in the coral Oculina patagonica

Abstract: Bleaching of corals is the result of the loss of their symbiotic algae (zooxanthellae) and/or their pigments. The supply of photoassimilates provided by the zooxanthellae to the corals declines during bleaching and reduces their ability to activate energy-costly processes. In the present study we compared regeneration capabilities of unbleached Oculina patagonica colonies (an encrusting Mediterranean stony coral) with those of bleached and partly bleached colonies. Using the 14 C point-labelling technique on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 35 publications
2
38
1
Order By: Relevance
“…This may be explained by a longer stress (bleaching) period experienced by polyps in the perimeter as compared with polyps at the colony center, leading to their death. Fine et al (2002) reported termination of intra-colonial resource translocation toward bleached parts of O. patagonica colonies. It is possible that during bleaching there is a controlled 'blockage' of the unbleached colony section (colony center) from the bleached section (perimeter region).…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by a longer stress (bleaching) period experienced by polyps in the perimeter as compared with polyps at the colony center, leading to their death. Fine et al (2002) reported termination of intra-colonial resource translocation toward bleached parts of O. patagonica colonies. It is possible that during bleaching there is a controlled 'blockage' of the unbleached colony section (colony center) from the bleached section (perimeter region).…”
Section: Discussionmentioning
confidence: 99%
“…Disease has been shown to activate directional transport of photosynthates away from the affected area, as if to reduce nutrient availability to the infecting pathogen and restrict resource loss to polyps that cannot be saved (Roff et al 2006). Bleaching that reduces Symbiodinium densities by as little as 40% is capable of halting inter-module translocation of photosynthates altogether, effectively isolating each polyp to fend for itself during stress events (Fine et al 2002). Our results are consistent with the observed responses to other stressors where physiological integration aids in the stress response.…”
Section: Discussionmentioning
confidence: 99%
“…The inverse relationship between colony integration and bleaching suggests that the response to moderate thermal stress may be akin to moderate pre dation, injury, or disease, where integration among modules may contribute to the effectiveness of the colony-wide response by permitting unaffec ted polyps to aid those in distress or to selectively isolate damage and reallocate resources from non-vital life history functions (Pearse & Muscatine 1971, Rinkevich & Loya 1983, Fang et al 1989, Gladfelter et al 1989, Oren et al 1997, Fine et al 2002, Roff et al 2006. Lesion induction has been shown to activate directional transport of photosynthates toward the injured tissue from modules up to 10 cm away, and to reduce reproductive investment up to 15 cm away from the lesion (Oren et al 1997, 2001, Roff et al 2006.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In theory, a low proportion of affected branches similar to that observed in January could be obtained in the (Oren et al 1997(Oren et al , 2001KramarskyWinter and Loya 2000;Lirman 2000;Fine et al 2002). If reports of disease …”
Section: Resultsmentioning
confidence: 99%